1998
DOI: 10.1246/bcsj.71.1451
|View full text |Cite
|
Sign up to set email alerts
|

Selective PdZn Alloy Formation in the Reduction of Pd/ZnO Catalysts

Abstract: Temperature programmed reduction (TPR) experiments were carried out over Pd/ZnO with different Pd loadings. Combined results with an X-ray diffraction method and X-ray photoelectron spectroscopy showed that a Pd–Zn alloy with a structure of PdZn was selectively produced in the course of TPR of Pd/ZnO. It was suggested that hydrogen retained in Pd spilled over to ZnO. The ZnO was reduced to metallic Zn, being converted to PdZn. The molar amounts of the ZnO reduced were practically the same as the those of Pd lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 13 publications
4
37
1
Order By: Relevance
“…2 The Pd/ZnO and Cu catalysts perform similarly to form H 2 and CO 2 from methanol, but their catalytic activity differs notably from that of pure metallic Pd. 3,4 The high performance of Pd/ZnO catalysts was assigned to PdZn alloys recently identified as PdZn ͑1:1 Pd:Zn atomic ratio͒ and Pd 3.9 Zn 6.1 ; 5,6 catalytic properties of alloys formed by Pt and Zn are similar. 7 The electronic and geometrical structure of palladium and platinum alloys, mainly with transition metals in d 10Ϫx configurations as second component, was intensively studied due to the industrial importance of Pd and Pt.…”
Section: Introductionmentioning
confidence: 99%
“…2 The Pd/ZnO and Cu catalysts perform similarly to form H 2 and CO 2 from methanol, but their catalytic activity differs notably from that of pure metallic Pd. 3,4 The high performance of Pd/ZnO catalysts was assigned to PdZn alloys recently identified as PdZn ͑1:1 Pd:Zn atomic ratio͒ and Pd 3.9 Zn 6.1 ; 5,6 catalytic properties of alloys formed by Pt and Zn are similar. 7 The electronic and geometrical structure of palladium and platinum alloys, mainly with transition metals in d 10Ϫx configurations as second component, was intensively studied due to the industrial importance of Pd and Pt.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd-Zn catalytic system deserves a special interest because it is highly active and selective in methanol synthesis, acetylene hydrogenation, steam reforming and dehydrogenation of methanol, and related industrial processes [8][9][10][11][12]. Pd-Zn alloys, which are thought to be crucial for the catalytic behavior, are known to form upon reduction of the Pd/ZnO catalyst at rather high temperatures ( ‡ 500°C) when the catalyst was prepared according to the traditional procedure from the component salts.…”
Section: Introductionmentioning
confidence: 99%
“…As unsupported pure Pd exhibits only a poor selectivity 22 , the observed high activity and selectivity for CO 2 formation was ascribed to the formation of distinct PdZn, PdIn and PdGa alloys upon reductive activation at elevated temperatures 18 . Best characterized is the Pd/ZnO system, where alloy formation has been studied and confirmed by X-ray diffraction (XRD) 18,23 , temperature-programmed reduction (TPR) 18,23 and X-ray and ultraviolet photoelectron spectroscopy (XPS and UPS) [24][25][26] . Iwasa et al 23 observed PdZn alloy formation upon reduction at very low T (≥ 473 K).…”
mentioning
confidence: 99%